Luxury Brands in Digital Age - Keeping up With Changing Customers - Savić, Nataša; Zlatić, Marija; Cook, Gina, 1970-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This thesis investigates luxury brands in the digital age and ways to keep up with changing customers. The aim of this thesis is to analyze the relationship between the perceived value of luxury brands and the digitalization of luxury customers. A quantitative method approach using regression analysis was employed to study this relationship laying the foundation for recommendations on how to adapt to changing luxury customers. Results indicate that there is a relationship between the digitalization of luxury customers and the perceived value of luxury brands. This provides evidence that luxury brands are affected by the digitalization of their customers. Furthermore, the development of a luxury purchase index enables individual customers to be ranked according to their perceived value of luxury brands. The findings of this thesis are value specifically to managers and academics as they bring forward strategic considerations in a contemporary luxury brand management context.
Vedoucí práce: Marija Zlatić
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses